The effects of arsenic trioxide addition on the mechanical and geochemical properties of the cemented paste backfill - Amirhossein Mohammadi; Isabelle Demers; Mostafa Benzaazoua; Nicholas Beier (Results in Materials, 2023)
Cemented paste backfill (CPB) technology, a densified mixture of mine tailings, binding material, and water, thickens to form a non-settling paste that is transported to fill mined cavities. CPB could provide environmental advantages by preventing the release of contaminants through hydraulic binder stabilization/solidification. Up to now, only few studies have been carried out to examine the feasibility of arsenic (As) fixation within cemented paste backfills. The main objective of the current study is to assess the impacts of incorporating pure arsenic trioxide on the geomechanical and geochemical properties of cemented paste backfill. CPB samples were prepared using pure ground silica (Sil-Co-Sil®) mimicking mine tailings, general use (GU) cement, deionized water, and reagent-grade pure As2O3 at different arsenic contents (0, 5, 10, and 15%). The samples were cured for up to 28 days and unconfined compressive strength (UCS) tests were conducted after 7 and 28 days of curing. Moreover, to evaluate the geochemical behavior of the pastes, mixtures of GU cement, pure As2O3 (0–15%), and deionized water with the same proportions as the CPB samples were prepared and mixed for up to 28 days. Then, pH, EC and chemical composition of the mixtures were evaluated. Results showed that the addition of pure arsenic trioxide (as a partial substitution for pure silica) leads to a substantial decrease in the mechanical strength of the CPB samples. However, this adverse effect was more substantial for the arsenic content of 5 wt%. The strength of the As2O3-containing samples did not improve significantly after 7 days of curing and arsenic addition lowered the pH of the solutions Microstructural analysis using SEM proved the formation of some C–S–H gels that contained arsenic in their structures as well as some complex mixture of oxides for the case of the As2O3-cement mixtures.